2004
DOI: 10.5194/angeo-22-1047-2004
|View full text |Cite
|
Sign up to set email alerts
|

The solar wind plasma density control of night-time auroral particle precipitation

Abstract: Abstract. DMSP F6 and F7 spacecraft observations of the average electron and ion energy, and energy fluxes in different night-time precipitation regions for the whole of 1986 were used to examine the precipitation features associated with solar wind density changes. It was found that during magnetic quietness (|AL|<100 nT), the enhancement of average ion fluxes was observed at least two times, along with the solar wind plasma density increase from 2 to 24 cm −3 . More pronounced was the ion flux enhancement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Borovsky et al (1998) showed that the solar wind material reaches the near-Earth nightside plasma sheet in about 4 h, which enhances particle precipitating fluxes and diminishes the average energy of precipitating ions and electrons. In general, when the number density of the solar wind increases, the energy flux of precipitating electrons and hence auroral luminosity in emission (1NG N 2 + ) of 391.4 nm are reduced (Vorobjev et al 2004). Consequently, the electron density and conductivity in the E layer of the ionosphere are also reduced, as well as the intensity of ionospheric and fieldaligned currents, and auroral arcs gradually vanish.…”
Section: Discussionmentioning
confidence: 99%
“…Borovsky et al (1998) showed that the solar wind material reaches the near-Earth nightside plasma sheet in about 4 h, which enhances particle precipitating fluxes and diminishes the average energy of precipitating ions and electrons. In general, when the number density of the solar wind increases, the energy flux of precipitating electrons and hence auroral luminosity in emission (1NG N 2 + ) of 391.4 nm are reduced (Vorobjev et al 2004). Consequently, the electron density and conductivity in the E layer of the ionosphere are also reduced, as well as the intensity of ionospheric and fieldaligned currents, and auroral arcs gradually vanish.…”
Section: Discussionmentioning
confidence: 99%